A Structured Scaffold Featuring Biomimetic Heterogeneous Architecture for the Regeneration of Critical-Size Bone Defects - Wang, Lingjun; Mao, Jiannan; Cai, Feng; Tang, Jincheng; Xi, Kun; Feng, Yu; Xu, Yichang; Liang, Xiao; Gu, Yong; Chen, Liang (Frontiers in Bioengineering and Biotechnology, 2022)
Regeneration of critical-size bone defect on long bones has remained significant challenge due to its complex anatomic structure and vascular network. Current forms of biomaterial with homogenous structure and function could hardly simultaneously satisfy the need of osteogenesis and angiogenesis in such circumstance. In current study, a heterogenous biomimetic structured scaffold was constructed with the help of 3D print mold to simultaneously mimic outer/inner periosteum and intermediate bone matrix of natural long bone. Owing to the reinforcement via modified mesoporous bioactive glass nanoparticles (MBGN), enhance structural stability and effective osteogenic capacity could be achieved for the intermediate layer of this scaffold. On the other hand, GelMA incorporated with VEGF-loaded liposome exhibiting controlled release of angiogenic factor was applied as the inner and outer layer of the scaffold. The produced heterogenous structured scaffold has exhibited effective performance on guiding bone regeneration and restoration of natural bone anatomic structure, rendering it a promising candidate in future orthopedic clinics.